Evaluación de alcaloides de chocho (Lupinus mutabilis Sweet) para el control de antracnosis (Colletotrichum sp.) en chocho, en condiciones de laboratorio. Salache, Latacunga, Cotopaxi 2021. - Ríos Madril, María Ipatia (2023)
In the study titled "Evaluation of lupine alkaloids (Lupinus mutabilis Sweet) for the control of anthracnose (Colletotrichum sp.) in lupine, under laboratory conditions. Salache, Latacunga, Cotopaxi 2021" the alkaloids present in Lupinus mutabilis Sweet were evaluated. for its potential antifungal activity against Colletotrichum sp. These alkaloids were evaluated under laboratory conditions, for which we worked with 2 study factors A (type of macerated control and residual liquid from the hydrated lupine) * B (concentrations) + 2 controls (chemical and absolute). Concentrations at 25%, 50%, 75%, and 100% were evaluated, with a completely randomized block design with 10 treatments and three repetitions, obtaining a total of 30 experimental units. The variables under study were the percentage of mycelial inhibition, speed of mycelial growth and the color of the mycelium. The results obtained showed that the alkaloids present in lupine exhibited significant antifungal activity against Colletotrichum sp. A greater inhibition of fungal growth was demonstrated, so it was determined that the concentration of 50% of the macerate in the fifth data collection inhibited 60.44%; and the 75% concentration had an inhibition percentage of 66.87%; demonstrating that lupine macerated control type alkaloids could be used for the development of natural antifungal treatments in agriculture. In this study it emerged that the alkaloids present in lupine have a potential antifungal effect against Colletotrichum sp. These results could have important implications for the development of natural and sustainable methods of disease control in lupine crops.